Interleukin-10 modulates the synthesis of inflammatory mediators in the sensory circumventricular organs: implications for the regulation of fever and sickness behaviors - Harden Lois M; Rummel Christoph; Luheshi Giamal N; Poole Stephen; Gerstberger Rüdiger; Roth Joachim (Journal of Neuroinflammation, 2013)
Abstract Background Whereas the role played by interleukin (IL)-10 in modulating fever and sickness behavior has been linked to it targeting the production of pro-inflammatory cytokines in the circulation, liver and spleen, it is not known whether it could directly target the local production of pro-inflammatory cytokines within the sensory circumventricular organs (CVOs) situated within the brain, but outside the blood–brain barrier. Using inactivation of IL-10, we, therefore, investigated whether IL-10 could modulate the synthesis of pro-inflammatory cytokines within the sensory CVOs, in particular the organum vasculosum laminae terminalis (OVLT) and area postrema (AP). Findings Primary OVLT and AP microcultures were established from topographically excised rat pup brain tissue. The microcultures were pretreated with either IL-10 antibodies (AB) (10 μl/350 μl medium) or phosphate-buffered saline (PBS) (10 μl/350 μl medium) before being incubated with lipopolysaccharide (LPS) (100 μg/ml) or PBS in complete medium for 6 h. Supernatants were removed from the microcultures after 6 h of incubation with LPS and used for the determination of IL-6 and tumor necrosis factor (TNF)-α. Pre-treating the OVLT and AP microcultures with IL-10 antibodies significantly enhanced the LPS-induced increase in TNF-α and IL-6 in the supernatant obtained from the microcultures. Conclusions Our results show for the first time that the LPS-induced release of pro-inflammatory cytokines in cells cultured from the AP and OVLT can be modulated in the presence of IL-10 antibodies. Thus, we have identified that the sensory CVOs may have a key role to play in both the initiation and modulation of neuroinflammation.